Peran Madrasah Kabupaten Nunukan dalam Mengaktualisasikan Islam Berwawasan Kebangsaan untuk Meneguhkan Sikap Moderasi Beragama - Pahmuddin, M.; Eko Nani Fitriono (Institut Muslim Cendekia, 2025)
The aim of this research is to determine the role of madrasah in Nunukan Regency in efforts to internalize Islam with a national perspective to enforce religious moderation for their students. This research uses samples from several madrasah in Nunukan Regency, where the madrasah used as samples are considered to have applied national values ​​that are oriented towards a moderate attitude. The research method used is a descriptive qualitative approach. Data collection uses direct observation, interviews and documentation. The results of this research are: First, the methods or methods used by madrasas are varied in applying Islam with a national perspective which reinforces an attitude of religious moderation; MA Al-Anshari Nunukan, which is a school under the auspices of the Islamic Boarding School Foundation, has from the start instilled the attitude of hubb al-wathan min al-īman (loving the homeland is part of faith) in its students, so that religion and love of the nation and state are one unit. , while at MA YIIPS Sebatik Timur the teachers not only teach religious values ​​to students, but they also actively involve students in national holiday activities to commemorate the services of the nation's predecessors, so that students are born who have a spirit of nationalism. Learning related to nationality, such as Civics, is also used to instill Islamic values ​​with a national perspective in students as is done at MI Roudhatut Tarbiyah Nunukan. Second, the urgency of national insight in madrasas is that: it can be an effective tool in preventing radicalism, strengthening national identity, and can foster an active attitude towards mutual tolerance.